Nasal Placode Development, GnRH Neuronal Migration and Kallmann Syndrome - Cho, Hyun-Ju; Shan, Yufei; Whittington, Niteace C.; Wray, Susan (Frontiers in Cell and Developmental Biology, 2019)
The development of Gonadotropin releasing hormone-1(GnRH) neurons is important for a functional reproduction system in vertebrates. Disruption of GnRH results in hypogonadism and if occompanied by anosmia is termed Kallmann Syndrome (KS). From their origin in the nasal placode, GnRH neurons migrate along the olfactory-derived vomeronasal axons to the nasal forebrain junction and then turn caudally into the developing forebrain. Although research on the origin of GnRH neurons, their migration and genes associated with KS have identified multiple factors which influence development of this system, several aspects still remain unclear. This review discusses development of the olfactory system, factors that regulate GnRH neuron formation and development of the olfactory system, migration of the GnRH neurons from the nose into the brain, and mutations in humans with KS that result from disruption of normal GnRH/olfactory systems development.